The role of chamaejasmine in cellular apoptosis and autophagy in MG-63 cells. Issue 1 (15th January 2019) - Yang, Dawei; Zhang, Hao; Wu, Jianjun; Ma, Ruishuang; Li, Zongyu; Wang, Kunzheng; Yang, Fan
Abstract : Background: Osteosarcoma (OS) is the most common malignant neoplasm in children and adolescents with a very high propensity for local invasion and poor response to current therapy. Anti-cancer effect of chamaejasmine is newly discovered from Stellera chamaejasmine L. Our study focuses on investigating the effect of chamaejasmine on the cellular apoptosis, proliferation, autophagy, and the underlying mechanisms in MG-63. Methods: Our study investigated the concentration of chamaejasmine in MG-63 cells by MTT and verified that chamaejasmine inhibited cell invasion by transwell. We also used Hoechst staining as well as apoptotic associated-proteins in MG-63 cells. Meanwhile, we also detected the lysophagesome and autophagsome by Lysotracker. Adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) knockdown was performed with siRNA. Results: Our results show that chamaejasmine exerts cellular growth inhibition, pro-apoptotic and pro-autophagic effect via activating AMPK in MG-63 cells. Furthermore, chamaejasmine significantly increases autophagic cell via the inhibition of mammalian target of rapamycin (mTOR) and activation of AMPK signaling pathways. Administrated with chamaejasmine also induces reactive oxygen species (ROS) generation, indicating cross-talking between these two primary modes of programmed cell death. Conclusion: Our results show that chamaejasmine promotes apoptosis and autophagy by activating AMPK/mTOR signaling pathways with involvement of ROS in MG-63 cells. Chamaejasmine is a promising anti-cancer agent in OS treatment, and further studies are needed to confirm its efficacy and safety in vivo or other cancer cells.